2017
DOI: 10.3390/cancers9080101
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transition and MicroRNAs in Lung Cancer

Abstract: Despite major advances, non-small cell lung cancer (NSCLC) remains the major cause of cancer-related death in developed countries. Metastasis and drug resistance are the main factors contributing to relapse and death. Epithelial-to-mesenchymal transition (EMT) is a complex molecular and cellular process involved in tissue remodelling that was extensively studied as an actor of tumour progression, metastasis and drug resistance in many cancer types and in lung cancers. Here we described with an emphasis on NSCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 308 publications
(322 reference statements)
1
59
0
Order By: Relevance
“…Non‐small‐cell lung cancer has become one of the deadliest malignancies in the world, but the molecular mechanisms involved in NSCLC development are not fully understood. Recent studies revealed that miRNAs play vital roles in the tumorigenesis and progression of NSCLC . In the present study, we focused on the antimetastatic function of miR‐331‐3p in NSCLC.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Non‐small‐cell lung cancer has become one of the deadliest malignancies in the world, but the molecular mechanisms involved in NSCLC development are not fully understood. Recent studies revealed that miRNAs play vital roles in the tumorigenesis and progression of NSCLC . In the present study, we focused on the antimetastatic function of miR‐331‐3p in NSCLC.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies revealed that miRNAs play vital roles in the tumorigenesis and progression of NSCLC. 28 In the present study, we focused on the antimetastatic function of miR-331-3p in NSCLC. The abnormal expression of miR-331-3p has been found in many types of carcinomas, but the evidence on its biological functions in the tumorigenesis of these cancers is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…29 To investigate the potential value of this circRNA in NSCLC, loss-of-function experiments were performed to confirm the anti-proliferation and anti-metastasis roles of circCDR1as silencing in NSCLC, which was similar to the previous report by Zhang et al 16 Moreover, epithelial-to-mesenchymal transition has been regarded as an important mechanism involved in the regulation of development and metastasis of lung cancer. 30,31 Hence, whether circCDR1as can promote cell growth, migration and invasion by inducing epithelial-tomesenchymal transition should be explored in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more than 40% of patients with early‐stage NSCLC have received treatment will have relapses . It has been currently confirmed that the occurrence of lung cancer had a certain correlation with the abnormal expression of various oncogenes and tumour suppressors, yet the carcinogenic mechanisms of oncogenes and tumour suppressors are complicated . In recent years, a significant progress has been made in the study of lung cancer‐related genes.…”
Section: Introductionmentioning
confidence: 99%